CANVAS LMS: OPPORTUNITIES AND FEATURES - Nalyvaiko, Oleksii; Vakulenko, Anastasiia (Educological discourse, 2021)
The sphere of education has been recently facing gradual changes in approaches and attitudes of all its participants to the process of studying. Rapid digitalization together with global life challenges such as the Covid-19 pandemic gets technology to be used together with traditional means of education in order to meet the needs of today's learners not only in a painless but also in a favourable way. The article considers the necessity to modernize the traditional process of studying and optimize it for learners, who deal with individual or forced distance study, caused by the pandemic as well. The up to date change implementation can be possibly accomplished with the help of specialized applications and web systems, particularly the online course platform Canvas, which stands in the focus of our paper. Previous studies and researches connected with similar and / or the same platform are mentioned briefly. The article also reveals technical capability and features of the Canvas system, presents the investigation of its conformity with students’ current needs through our analysis of its advantages and disadvantages and describes its pros and cons not only from the point of view of students, who are considered to be the representatives of the main category or platform users, but also considering teachers’ experience and impressions of Canvas as a primary or a subsidiary educational system with courses. The readers of this article may get acquainted with the main elements of the Canvas platform structure, learn about their characteristics and decide whether to approve or disapprove such an alternative to outdated course attendance. Furthermore, the research includes a survey conducted among 50 students, who had already used the platform in appliance with their curriculum and were asked to share their impressions starting from logging in to giving an overall review of this concentration of online courses. In the final analysis we provide the readers of the article with a general conclusion about the platform, its conformity with the requirements of the educational system and learners’ needs specifically.